Netter's essential histology : with correlated histopathology / William K. Ovalle, Patrick C. Nahirney - Ovalle, William K.
The approach to acquiring a firm understanding when comparing normal versus abnormal structure of cells and tissues continues to be a challenging aspect of histology, especially as it relates to medicine and disease diagnosis. Accurate identification of cellular alterations in pathologic tissues that are described in standard textbooks and directly relating them to their actual microscopic appearance is often a demanding task. In this updated and revised third edition of Netter's Essential Histology, we approach these challenges by incorporating new pages at the end of each chapter that focus on histopathology and which portray clinically abnormal structures. Our primary aim is to pinpoint the important pathologic alterations detected in cells and tissues in many common and clinically relevant disorders. In these new pages, we include low- to-high-magnification examples of tissues combined with classic Netter illustrations to succinctly highlight salient features seen in histopathology